Surgical Exposure Technique for Volar Locking Plate Fixation of Distal Radius Fractures in Patients with Flexor Carpi Radialis Brevis Muscle Anomaly - Hiroshi Ninomiya; Makito Watanabe; Kazunari Kamimura (Case Reports in Orthopedics)
The flexor carpi radialis brevis (FCRB) muscle, considered a rare anomaly, is not well known among orthopedic surgeons. The indications for volar locking plates to treat distal radius fractures have recently expanded, and, as a result, encounters with the FCRB are becoming more common. However, few studies have described how to retract an FCRB. Here, we describe seven of 264 patients with FCRB who underwent surgery for distal radius fractures. In one case, the retracted FCRB interfered with the internal fixation. The presented cases demonstrate that the radial retraction of an FCRB with a large muscle belly enables favorable exposure of the distal radius.